Conserved Cytoplasmic Loops Are Important for both the Transport and Chemotaxis Functions of PcaK, a Protein from Pseudomonas putida with 12 Membrane-Spanning Regions - Ditty, Jayna L. (American Society for Microbiology, 1999)
Chemotaxis to the aromatic acid 4-hydroxybenzoate (4-HBA) by Pseudomonas putida is mediated by PcaK, a membrane-bound protein that also functions as a 4-HBA transporter. PcaK belongs to the major facilitator superfamily (MFS) of transport proteins, none of which have so far been implicated in chemotaxis. Work with two well-studied MFS transporters, LacY (the lactose permease) and TetA (a tetracycline efflux protein), has revealed two stretches of amino acids located between the second and third (2-3 loop) and the eighth and ninth (8-9 loop) transmembrane regions that are required for substrate transport. These sequences are conserved among most MFS transporters, including PcaK. To determine if PcaK has functional requirements similar to those of other MFS transport proteins and to analyze the relationship between the transport and chemotaxis functions of PcaK, we generated strains with mutations in amino acid residues located in the 2-3 and 8-9 loops of PcaK. The mutant proteins were analyzed in 4-HBA transport and chemotaxis assays. Cells expressing mutant PcaK proteins had a range of phenotypes. Some transported at wild-type levels, while others were partially or completely defective in 4-HBA transport. An aspartate residue in the 8-9 loop that has no counterpart in LacY and TetA, but is conserved among members of the aromatic acid/H(+) symporter family of the MFS, was found to be critical for 4-HBA transport. These results indicate that conserved amino acids in the 2-3 and 8-9 loops of PcaK are required for 4-HBA transport. Amino acid changes that decreased 4-HBA transport also caused a decrease in 4-HBA chemotaxis, but the effect on chemotaxis was sometimes slightly more severe. The requirement of PcaK for both 4-HBA transport and chemotaxis demonstrates that P. putida has a chemoreceptor that differs from the classical chemoreceptors described for Escherichia coli and Salmonella typhimurium.